2021
DOI: 10.1002/csr.2148
|View full text |Cite
|
Sign up to set email alerts
|

How corporate social responsibility can incentivize top managers: A commitment to sustainability as an agency intervention

Abstract: Over the past few years, scholarly interest in corporate social responsibility (CSR) has been increasing. However, research on the relationship between CSR and firm performance has revealed a complicated relationship. In this paper, we argue that part of the basis for the generally positive relationship between CSR and firm performance might come from a reduction in agency costs. Relying on behavioral agency theory, we construct a model in which CSR moderates the impact of the agency problem on specific firm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 149 publications
(278 reference statements)
0
21
0
Order By: Relevance
“…should win the support of top management for success. Findings of Greiner and Sun (2021) reveal that top managers may be willing to forgo the practical benefits of opportunism, including shirking or the taking of perquisites, in exchange for the personal satisfaction that comes from serving what they perceive to be a higher good. Likewise, when pertaining to corporate social responsibility (CSR), Khediri (2021) highlights the important role of CSR in determining firms' investment behavior and efficiency.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…should win the support of top management for success. Findings of Greiner and Sun (2021) reveal that top managers may be willing to forgo the practical benefits of opportunism, including shirking or the taking of perquisites, in exchange for the personal satisfaction that comes from serving what they perceive to be a higher good. Likewise, when pertaining to corporate social responsibility (CSR), Khediri (2021) highlights the important role of CSR in determining firms' investment behavior and efficiency.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Some institutions believe that if they take on social responsibilities, the burden and economic cost of running their organizations would eventually increase. Therefore, such institutions are unwilling to undertake social responsibility related practices and are predicted to gradually lose customers (Greiner & Sun, 2021;Ullah & Sun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported that the adoption of CSR activities helps banks earn better reputations and increased BL, as these banks have a leading role in modifying the quality of life of the most in need in society. Their adoption of CSR activities not only leads to increased profits, but the betterment of the general welfare of individuals (Streimikiene & Ahmed, 2021;Greiner & Sun, 2021;Ullah & Sun, 2020;Hafez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Under this approach, sustainability accounting and management are seen to be tools to mitigate agency problems. However, these tools are costly and empirical research is not conclusive about their impact (Kim et al, 2012;Greiner and Sun, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, BAT argues that agents are bounded-rational and loss-, risk-and uncertainty-averse while they do not only seek for financial rewards but also seek social, ideological or psychological incentives (Pepper and Gore, 2015). In this light, sustainability accounting and management can be seen as an intervention tool which provides the agents with important non-financial incentives to act less opportunistically and hence align their actions with the interest of the company (Greiner and Sun, 2021). In this manner, BAT calls for taking into consideration intrinsic, non-financial (together with extrinsic, financial) motives to theoretically explain and practically incentivise agents' actions.…”
Section: Introductionmentioning
confidence: 99%